Evaluating the Geographic in GIS. - Guan, Weihe W.; Wilson, Matthew W.; Knowles, Anne K. (Geographical Review, 2019)
Despite several decades of discussion and debate around the role of GIS in the discipline of Geography, it would be a stretch to argue that GIS has not irreversibly altered the discipline, both in the scope of research and teaching as well as in the wider imagination of a general public. However, it remains a challenge to incorporate the range of geographic knowledge, born of a diversity of modalities, into operational insights and analytical pre‐conditions in a GIS. To be certain, some irreconcilability between GIS and geographical inquiry is to be expected, epistemologically speaking. In what follows, we consider what might be meant by a shift to geographic analysis as scholars from disciplines in the humanities and social sciences turn to GIS as a method of observation, interpretation, analysis, and representation. In this context, we engage in a thought experiment and offer some commentary, fixing the notion of information system, while opening the geographic in GIS to more variable understanding. The point is to pursue greater development of GIS theory and method, encompassing, while not reducing, scientific, social scientific, and humanities research.